A new V-shaped 2H-imidazole-based spirocyclic fluorophore: Aggregation-induced emission, twisted intramolecular charge transfer, and high responsiveness to trace water and acid. (October 2021) - Du, Feiyue; Li, Dongqin; Ge, Sheng; Xie, Shumei; Tang, Mi; Xu, Ziqiang; Wang, Erjing; Wang, Shimin; Tang, Ben Zhong
Abstract: Design and synthesis of organic solid-state emissive materials have attracted wide attentions due to their potential applications in organic light-emitting diodes (OLEDs), chemo-/bio-sensing, organic lasers, electronic ink, etc. Herein, a V-shaped 2H -imidazole-based spirocyclic fluorophore, DPS-DPA, was efficiently prepared. DPS-DPA shows solvatochromism behaviors. With the continuous addition of anti-solvent water to acetonitrile solution of DPS-DPA, the emission of DPS-DPA first became faint, and then profoundly enhanced, demonstrating the characteristics of twisted intramolecular charge transfer and aggregation-induced emission. To our surprise, the fluorescence of DSP-DPA in solution would be greatly decreased even in the presence of trace amount of water, indicating that DPS-DPA has a high responsiveness to water. Moreover, the emission of DPS-DPA can be quenched by trifluoroacetic acid and recovered after triethylamine addition, realizing reversible fluorescent writing and erasing. Such attributes make the material find wide applications in many areas such as solvent quality control, smart design, and optoelectronic devices. Highlights: Design and synthesis of organic solid-state emissive materials have attracted wide attentions due to their potential applications in organic light-emitting diodes (OLEDs), chemo-/bio-sensing, organic lasers, electronic ink, etc. Herein, we report a new type of V-shaped 2H-imidazole-based spirocyclic fluorophore, DPS-DPA, exhibits the characteristics of twisted intramolecular charge transfer and aggregation-induced emission. The solid-state quantum yield of DPS-DPA is as high as 42.5%. Additionally, the fluorescence of DSP-DPA in solution would be greatly decreased even in the presence of trace amount of water, indicating that DPS-DPA has a high responsiveness to trace water. Moreover, the emission of DPS-DPA can be quenched by trifluoroacetic acid and recovered after triphenylamine addition, realizing fluorescent writing and erasing cycle. The main findings of the manuscript can be summarized as follows: (1) DPS-DPA can be easily synthesized through simple three-component Debus-Radziszewski imidazole synthesis followed by Pd-catalyzed coupling reaction, and the yield is higher than 75%. (2) DPS-DPA shows obvious solvochromism. In particular, the photoluminescence can be changed from 443 nm in toluene to 560 nm in acetonitrile, indicating a high sensitivity to solvent polarity. (3) DPS-DPA exhibited aggregation-induced emission characteristic. The solid-state quantum yield can be as high as 42.5%, which is rarely seen in spirocyclic organic optoelectronic materials. (4) DPS-DPA shows high sensitivity to trace amount of water in water-miscible solvents including THF, DMF, 1, 4-dioxane, and acetonitrile. In the lower water content, the PL intensity change shows a linear (THF) or an exponential (acetonitrile) curve. DPS-DPA was used to quantify the water content of several solvents commonly used in chemistry lab. (5) The fluorescence can realize writing/erasing cycle under the treatment with trifluoroacetic acid/triethylamine. Given the simple synthesis and diverse performance of DPS-DPA, this study could provide us a clue to the construction of new-type organic spirocyclic optoelectronic materials for solid-state emission, smart control, and sensing. We expect that our results will be of interest for researches from a wide range of disciplines. Thus, we wish that this work could be considered for publication on Dyes and Pigments.